Agreement analysis of pentacam and lenstar in measurement of keratometry, anterior chamber depth and lens thickness / Azlindarita A Mohd Abdullah … [et al.] - Mohd Abdullah, Azlindarita A; Mustafa, Norasyikin; Loo, Voon Pei; Subrayan, Visvaraja (Faculty of Medicine, 2016)
Introduction: To assess the agreement of the Scheimpflug camera system Pentacam with the optical low-coherence reflectometry (OLCR) device LENSTAR LS900 in measuring anterior segment biometry. Methods: This is a prospective, non- randomized, comparative analysis study. Patients with age-related nucleus sclerosis cataract who fulfilled the inclusion criteria and attended the Ophthalmology Clinic in University of Malaya Medical Centre (UMMC) between December 2011 and March 2012 were recruited. The keratometer, anterior chamber (AC) depth and lens thickness were measured with both methods Pentacam and Lenstar. Results: 223 eyes of 125 patients were analysed. There was an agreement in the keratometer, anterior chamber depth and lens thickness measurement between the two devices. There was a significant correlation between K-reading as measured by both devices, at 0.05 significant level, with correlation coefficient of 0.904 and p < 0.001. The correlation coefficient of AC depth measurement between Pentacam and Lenstar at 0.05 significant level was 0.992 (p < 0.001). From the 124 eyes in which the lens thickness were measureable with both Pentacam and Lenstar, a positive correlation was noted (correlation coefficient of 0.585, p-value of < 0.001). There was no significant difference in the three parameters between males and females and among Malay, Chinese and Indian patients. Conclusions: There is a statistical agreement in the anterior segment biometry measurements between the Pentacam and the Lenstar